2019
DOI: 10.1111/nph.16272
|View full text |Cite|
|
Sign up to set email alerts
|

Anthocyanin Fruit encodes an R2R3‐MYB transcription factor, SlAN2‐like, activating the transcription of SlMYBATV to fine‐tune anthocyanin content in tomato fruit

Abstract: Anthocyanin fruit (Aft) and atroviolacea (atv) were characterized in wild tomato and can enhance anthocyanin content in tomato fruit. However, the gene underlying the Aft locus and the mechanism by which Aft and atv act remain largely unknown.In this study, the Aft locus was fine-mapped to an approximately 145-kb interval on chromosome 10, excluding SlAN2 (Solyc10g086250), SlANT1 (Solyc10g086260) and SlANT1like (Solyc10g086270), which have previously been suggested as candidates. Thus, the R2R3-MYB transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
120
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(128 citation statements)
references
References 71 publications
8
120
0
Order By: Relevance
“…For example, the expression of the peach ( Prunus persica ) R2R3‐MYB gene MYB18 is induced by R2R3‐MYB transcriptional activators to balance anthocyanin and proanthocyanidin accumulation (Zhou et al ., 2019). In tomato fruit, the SlAN2‐like R2R3‐MYB TF activates the transcription of SlMYBATV , which encodes a transcriptional repressor, to fine‐tune anthocyanin biosynthesis (Yan et al ., 2020). In the present study, we detected the upregulated expression of the R2R3‐MYB transcriptional repressor gene PpMYB140 in PpERF105 ‐OX pear calli (Figure S6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the expression of the peach ( Prunus persica ) R2R3‐MYB gene MYB18 is induced by R2R3‐MYB transcriptional activators to balance anthocyanin and proanthocyanidin accumulation (Zhou et al ., 2019). In tomato fruit, the SlAN2‐like R2R3‐MYB TF activates the transcription of SlMYBATV , which encodes a transcriptional repressor, to fine‐tune anthocyanin biosynthesis (Yan et al ., 2020). In the present study, we detected the upregulated expression of the R2R3‐MYB transcriptional repressor gene PpMYB140 in PpERF105 ‐OX pear calli (Figure S6).…”
Section: Discussionmentioning
confidence: 99%
“…A luciferase assay indicated that although PpMYB140 can directly inhibit PpANS expression, the transcriptional repression is enhanced by the interaction between PpMYB140 and bHLH3 (Figure 5c). In tomato ( Solanum lycopersicum ), SlMYBATV competes with the SlAN2‐like TF for the interaction with SlJAF13 (i.e., bHLH TF) (Yan et al ., 2020). In our study, a firefly luciferase complementation imaging assay and an examination of transiently transformed ‘Hongzaosu’ pear fruit verified that PpMYB140 competes with PpMYB114 for the binding to bHLH3 and inhibits anthocyanin biosynthesis (Figures 5d and 6).…”
Section: Discussionmentioning
confidence: 99%
“…To understand the mechanism leading to differential gene expression in red- and white-skinned genotypes, the coding and promoter sequences of the RsPAP2 gene were compared among the different radish genotypes. It was found that there were three nonsynonymous SNPs in the coding region of RsPAP2 , but two of the SNPs were only identified in three genotypes with different skin colors, and one SNP was not located in a conserved domain, which similar to the situation of the SlAN2-like gene in tomato fruit 39 . However, a total of ten SNPs and four base deletions were found in the 948 bp promoter region, among which two of the base deletions (“T” at 849 bp and “A” at 850 bp) were consistently found among the red-skinned genotypes with the exception of one genotype, “NAU-123” (Table S3 ).…”
Section: Discussionmentioning
confidence: 96%
“…However, a total of ten SNPs and four base deletions were found in the 948 bp promoter region, among which two of the base deletions (“T” at 849 bp and “A” at 850 bp) were consistently found among the red-skinned genotypes with the exception of one genotype, “NAU-123” (Table S3 ). Cases of such insertions or deletions are also found in blood orange, apple, and tomato 39 41 . Although further experimental evidence is needed, this deletion in the promoter region might contribute to the differential expression of RsPAP2 and affect ATC biosynthesis in radish.…”
Section: Discussionmentioning
confidence: 99%
“…In these systems, an R2R3 Myb, bHLH, and WDR "MBW" transcriptional regulon has been identified as a central regulator for color patterning, controlling both orange carotenoid and purple/red anthocyanin deposition (Sagawa et al 2016;Ludwig et al 1989;Albert et al 2014). In contrast to floral systems, relatively little is known about the genetics of color patterning in vegetative organs; however, current knowledge including genetic mapping of pigmentation variants for leaves, roots, and fruits (Albert et al, 2015;Yan et al, 2020;Xu et al, 2020;Yu et al, 2020) and ectopic expression of floral regulators in vegetative tissue (Albert et al, 2020), indicates that the transcriptional MBW regulon is broadly involved in pigmentation patterning across diverse organs.…”
Section: Discussionmentioning
confidence: 99%